2020
DOI: 10.1080/10408363.2020.1770685
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers associated with COVID-19 disease progression

Abstract: The coronavirus disease 2019 (COVID-19) pandemic is a scientific, medical, and social challenge. The complexity of the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is centered on the unpredictable clinical course of the disease that can rapidly develop, causing severe and deadly complications. The identification of effective laboratory biomarkers able to classify patients based on their risk is imperative in being able to guarantee prompt treatment. The analysis of recently published studies hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

70
752
10
65

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 765 publications
(897 citation statements)
references
References 112 publications
70
752
10
65
Order By: Relevance
“…Published literature indicates that D-Dimer levels were signi cantly higher among those with severe disease. 1,5,7,10,21 This discrepancy may be due to the homogenous nature of our study population (severe COVID-19 patients admitted to ICU) while the majority of other studies had patients with mild, moderate and severe disease. It has been reported that patients with non-severe disease have a lower level of D-Dimer as compared to those with severe disease.…”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“…Published literature indicates that D-Dimer levels were signi cantly higher among those with severe disease. 1,5,7,10,21 This discrepancy may be due to the homogenous nature of our study population (severe COVID-19 patients admitted to ICU) while the majority of other studies had patients with mild, moderate and severe disease. It has been reported that patients with non-severe disease have a lower level of D-Dimer as compared to those with severe disease.…”
Section: Resultsmentioning
confidence: 82%
“…Multiple factors have been proposed for the complex and ill-de ned course of the illness. 5 In the most of the cases, the disease is fairly mild, while in the rest it results in severe disease leading to multiorgan failure and death. 6 Apart from gender, age, blood groups, and co-morbidities, a plethora of laboratory markers have been investigated to predict the course and outcome of the disease.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, there was neither correlation between CRP and albumin (-0.3277) nor between ESR and albumin (-0.0504) ( Table 1). Studies have revealed no/slight increase of ESR and CRP 36,38,39 while other studies showed inconsiderable decrease of serum albumin in mildmoderate COVID-19 patients 38,40 . Most importantly no studies conducted on post recovery patients addressing those markers.…”
Section: Resultsmentioning
confidence: 97%
“…Ponti et al 36 found the severity of COVID-19 is positively correlated with ESR and CRP, while no study on both biomarkers after the recovery of COVID-19 patients has been recorded yet. Our data has revealed a positive correlation between ESR and CRP (R 2 =0.85) in severe COVID-19 post recovery patients.…”
Section: Resultsmentioning
confidence: 98%
“…Such patients need close monitoring and early transfer to the hospital. Various biomarkers, especially in ammatory markers like C-reactive protein (CRP), ferritin, brinogen, D-dimer and Interleukin 6 (IL-6) are associated with Covid-19 progression [10,11]. According to known evidence, IL-6 is superior to CRP and other markers of in ammation in predicting respiratory failure in Covid-19 [16,17].…”
Section: Introductionmentioning
confidence: 99%